Analysis of Factors Affecting Community on the Use of Non-Cash Payment Tools in Taman District, Sidoarjo Regency - Nurdina; R. Bambang Dwi Waryanto; Nurul Afiyah (Universitas Dinamika, 2021)
The purpose of the study was to examine the effect of perceived benefits, convenience, trustworthiness, and risk on the use of non-cash payment instruments in Taman Sub-district, Sidoarjo Regency. The Theory Acceptance Model (TAM) is used as the theoretical basis for the research. The research sample is people who transact at Alfamart, Indomaret, McDonald's Geluran, and Alfamidi in Taman sub-district, Sidoarjo district. Multilevel random sampling method. The questionnaires distributed were 100 respondents. The results showed that trust had no effect, while the benefits, convenience, and risk had an effect on noncash payment instruments.